2018
DOI: 10.1186/s12943-018-0905-y
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based assessment and network analysis of targeting 14-3-3 proteins in prostate cancer

Abstract: Developing combination therapy for castrate-resistant prostate cancer (CRPC) may require exploiting new drug targets outside androgen receptor and PI3K / AKT / mTOR signal transduction pathways implicated in prostate cancer (PCa) progression. One such possible new target is YWHAZ of the 14-3-3 protein family as this gene has prognostic significance for metastatic CRPC patients. However, there are no small molecules targeting YWHAZ commercially available. Hence, we explored whether the small molecule BV02 targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…36 Previous studies have implicated 14-3-3ε as a cell enhancer factor that promotes cell proliferation in breast cancer cells, 12 gastric cancer SGC7901 cells, 37 and hepatocellular carcinoma 14 and as a potential novel genetic risk factor for HIV neurocognitive impairment, 24 major depressive disorder in males of the Chinese Han population, 38 and development of midline craniofacial structures. 39 Recently, Alex and colleagues 9 suggested that 14-3-3ε and other family members play an important role in the development and progression of PCa, indicating that it can be employed as a drug target in the treatment of PCa. In the present study, we found that 14-3-3ε is significantly upregulated in PCa cell lines and acts as a cell enhancer factor to promote PCa cell proliferation, migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…36 Previous studies have implicated 14-3-3ε as a cell enhancer factor that promotes cell proliferation in breast cancer cells, 12 gastric cancer SGC7901 cells, 37 and hepatocellular carcinoma 14 and as a potential novel genetic risk factor for HIV neurocognitive impairment, 24 major depressive disorder in males of the Chinese Han population, 38 and development of midline craniofacial structures. 39 Recently, Alex and colleagues 9 suggested that 14-3-3ε and other family members play an important role in the development and progression of PCa, indicating that it can be employed as a drug target in the treatment of PCa. In the present study, we found that 14-3-3ε is significantly upregulated in PCa cell lines and acts as a cell enhancer factor to promote PCa cell proliferation, migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…8 This family may be used as a novel target for the diagnosis and treatment of PCa. 9 14-3-3 Proteins are a family of conserved regulatory molecules that are expressed in eukaryotic cells. 10 14-3-3 Proteins regulate intracellular signaling pathways through the phosphorylation of serine/threonine motifs of target proteins that are related to signal transduction, protein trafficking, cell cycle, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…14-3-3ζ has been identified as an oncogene of several tumors, and overexpression of 14-3-3ζ was frequently detected in lung adenocarcinoma tissues, and was significantly associated with lymph node metastasis and adverse outcomes [32]. In the study of prostate cancer, the 14-3-3 family of YWHAZ, which is associated with the prognosis of metastatic prostate cancer, can be used as a target for prostate cancer treatment [33]. Related experiments in breast cancer found that phosphorylation of BAD at S118 stimulates the survival pathway, which in turn phosphorylates BAD at S99, resulting in binding to the 14-3-3 protein, thereby affecting the proliferation of breast cancer tumor cells [34].…”
Section: Discussionmentioning
confidence: 99%